Wilsonowska koncepcja bezpieczeństwa i rozbrojenia - Kiwerska, Jadwiga (Acta Universitatis Lodziensis. Folia Historica, 1983)
The problem of security and disarmament received a great deal of attention in W. Wilson’s political concepts. It was, first of all, a result of requirements posed by the First World War as well as needs and considerations of the United States wishing to participate actively in the international political events. The character of Wilson's concepts was strongly affected by personality and aspirations of 28th president of the United States.